THU0413 Magnetic resonance imaging of hands and feet joints of ACPA positive persons without clinical arthritis. (23rd January 2014) - Krabben, A.; Stomp, W.; Brakenhoff, L.K.P.M.; van der Heijde, D.M.F.M.; Bloem, J.L.; Huizinga, T.W.J.; Reijnierse, M.; van der Helm-van Mil, A.H.M.
Abstract : Background: Until recently, the development of clinical detectable arthritis was considered as the start of Rheumatoid Arthritis (RA). Several studies have revealed that anti-citrullinated peptide antibodies (ACPA) can be present and mature years before arthritis develops and that markers of systemic inflammation and bone degradation are also elevated in the preclinical phase. These data suggest that the process of RA starts earlier than clinical arthritis occurs. It is however unknown whether local subclinical inflammation is present in the preclinical phase. MRI is sensitive in detecting subclinical inflammation. Objectives: To investigate whether there is subclinical inflammation in painful joints in ACPA-positive arthralgia patients without clinical arthritis. Methods: Painful hand or feet joints of 15 ACPA positive patients without clinical arthritis were imaged, as well as comparable small joints at a non-painful site. In addition, for further comparisons, small joints of 6 ACPA positive RA patients and 8 persons with inflammatory bowel disease but without arthralgia were evaluated. Imaging was performed on a MSK Extreme 1.5T extremity MRI (GE, Wisconsin, USA). Acquired sequences were coronal T1, coronal T2 fat sat and coronal and axial T1 fat sat after IV Gadolinium-chelate administration. Scoring was performed by two trained readers according to the OMERACT RAMRIS scoring method. The mean scores of the two readers were analyzed. Analyses were performed on joint level (MCP, PIP, wrist or MTP joints). Results: The mean total RAMRIS score of the MCP/PIP joints in the persons without arthralgia, the painful joints of ACPA-positive arthralgia patients and painful joints of ACPA-positive RA patients were 0.1, 0.8 and 3.7 respectively (Kruskal-Wallis test, p=0.004). The scores of the painful joints and painless joints in ACPA-positive arthralgia patients were strongly correlated (rs =0.75) and not different between the groups (mean 1.9 and 2.4, respectively). The mean total RAMRIS scores of the wrist and MTP joints in ACPA-positive arthralgia were 4.2 and 2.1, which was lower than those of RA patients (7.8 and 2.8 respectively). Unfortunately the wrist and MTP joints of the controls were not imaged. Conclusions: The present data suggest that, when compared to both controls and ACPA-positive RA, patients with arthralgia with ACPA but no clinical arthritis have subclinical inflammation locally at the site of the pain. Furthermore, the non-painful small joints show abnormalities that are comparable in severity to that of the painful joints. Disclosure of Interest: None Declared